An Analytical Approach to Visitor Carrying Capacity and Conservation: The Pindul Cave of Yogyakarta - Siregar, Aisyah Astinadia (International Journal of Green Tourism Research and Applications, 2025)
Tourism in natural attractions, such as Pindul Cave in Indonesia, offers significant economic and recreational benefits while posing challenges to environmental sustainability and visitor experience. The increasing influx of tourists to ecotourism destinations like Pindul Cave raises concerns over environmental degradation, overcrowding, and declining visitor satisfaction. This study aims to assess the sustainable tourism carrying capacity of Pindul Cave by analyzing visitor capacity concerning environmental conservation and tourist comfort. Employing a mixed-methods research design, the study integrates quantitative survey data with qualitative insights from interviews and field observations. Respondents include domestic and international tourists, local community members, and key tourism stakeholders involved in site management. Data collection focuses on visitor behavior, perceived environmental impact, and current tourism management practices. Using established carrying capacity models, the analysis identifies the maximum number of visitors the site can accommodate without compromising environmental integrity or the quality of the tourist experience. Findings indicate that Pindul Cave is nearing its sustainable carrying capacity threshold. If unmanaged, continued growth in visitation may lead to negative ecological impacts and diminished tourist satisfaction. The study underscores the urgent need for regulatory strategies to manage visitor flow and promote sustainable tourism practices. It offers practical recommendations for local authorities, tourism managers, and policymakers to balance conservation goals with economic development through responsible ecotourism planning.